Development of an Azonexus- and Competibacter-enriched phosphate-accumulating community in the anaerobic/anoxic sequencing batch reactor: Cooperative denitrification - Alexander Dorofeev; Anna Pelevina; Evgeny Gruzdev; Alexey Beletsky; Yulia Berestovskaya; Yury Litti; Andrey Mardanov; Nikolai Pimenov (Bioresource Technology, 2026)

Surface Problem: Unveiling Extracellular Vesicles Surface Markers and Their Implications for Central Nervous System Diseases’ Diagnosis and Treatment - Stanislav Gruzdev; Alexander Yakovlev (Molecular Neurobiology, 2026)

Muskox status, recent variation, and uncertain future - Christine Cuyler; Janice Rowell; Jan Adamczewski; Morgan Anderson; John Blake; Tord Bretten; Vincent Brodeur; Mitch Campbell; Sylvia L. Checkley; H. Dean Cluff; Steeve D. Côté; Tracy Davison; et al. (Ambio, 2020)

Microbial processes of the carbon and sulfur cycles in an ice‐covered, iron‐rich meromictic lake S vetloe ( A rkhangelsk region, R ussia) - Alexander S. Savvichev; Natalia M. Kokryatskaya; Svetlana A. Zabelina; Igor I. Rusanov; Elena E. Zakharova; Elena F. Veslopolova; Olga N. Lunina; Ekaterina O. Patutina; Boris K. Bumazhkin; Denis S. Gruzdev; Pavel A. Sigalevich; Nikolay V. Pimenov; et al. (Environmental Microbiology, 2017)
Summary Biogeochemical, isotope geochemical and microbiological investigation of Lake Svetloe (White Sea basin), a meromictic freshwater was carried out in April 2014, when ice thickness was ∼0.5 m, and the ice‐covered water column contained oxygen to 23 m depth. Below, the anoxic water column contained ferrous iron (up to 240 μμM), manganese (60 μM), sulfide (up to 2 μM) and dissolved methane (960 μM). The highest abundance of microbial cells revealed by epifluorescence microscopy was found in the chemocline (redox zone) at 23–24.5 m. Oxygenic photosynthesis exhibited two peaks: the major one (0.43 μmol C L −1 day −1 ) below the ice and the minor one in the chemocline zone, where cyanobacteria related to Synechococcus rubescens were detected. The maximum of anoxygenic photosynthesis (0.69 μmol C L −1 day −1 ) at the oxic/anoxic interface, for which green sulfur bacteria Chlorobium phaeoclathratiforme were probably responsible, exceeded the value for oxygenic photosynthesis. Bacterial sulfate reduction peaked (1.5 μmol S L −1 day −1 ) below the chemocline zone. The rates of methane oxidation were as high as 1.8 μmol CH 4 L −1 day −1 at the oxi/anoxic interface and much lower in the oxic zone. Small phycoerythrin‐containing Synechococcus ‐related cyanobacteria were probably involved in accumulation of metal oxides in the redox zone.